Perfil tóxico-farmacológico da administração da doxorrubicina em cães com tumor venéreo transmissível - Assumpção, Juliana Uruguay Corrêa Vidigal [UNESP] (2015)
Doxorubicin (DOX), the anthracycline family of chemotherapy is used in the treatment of various solid tumors in animals and humans, and is a second-line drug for the treatment of dogs, transmissible venereal tumor (TVT) resistant to other chemotherapeutic agents. Its therapeutic use is limited due to cardiotoxicity and myelosuppression, dose-dependent effects. The cardiotoxicity of DOX has been observed in healthy dogs, however, the pharmacokinetics and toxicity in this animal model subjected to the dosing regimen for the treatment of TVT have not been investigated. Also, there have been proposed new formulations containing the drug with the aim to improve efficacy and decrease toxicity. This study aimed to investigate the pharmacokinetic profile of DOX administered as hydrochloride at a dose of 30 mg / m2 every 21 days, in four cycles, by continuous infusion for 30 minutes in dogs with TVT (n = 10) as well as assess toxic effects through biochemical, hematological and urinalysis samples taken before and after exposure to chemotherapy.Still, this work proposed to evaluate the pharmacokinetic profile and systemic toxicity of DOX conveyed in microemulsion system in dogs with TVT treated under the same dose of DOX hydrochloride regime. For the investigation of the pharmacokinetic profile in both groups, a bioanalytical method performance liquid chromatography ultra efficiency (CLUE) for determining DOX was developed and validated. The bioanalytical method was appropriate confidence limits for application in the investigation of the pharmacokinetic profile, with limit of quantitation (LLQ) of 19 ng / mL and detection limit (LLD) of 9 ng / ml. Pharmacokinetic parameters of DOX calculated from the administration of the hydrochloride formulation, the first and fourth treatment cycle were: elimination half-life 30.7 and 19.16 hours; volume of distribution 652.18 and 397.45 L/kg and ...